VIRAL INFECTIONS IN CHILDREN SUFFERED FROM CISTIC FIBROSIS - N.N. Nisevich; E.V. Sereda; N.S. Selyutina; O.V. Kriger; I.N. Nikishtsev; N.L. Agoshkova (Педиатрическая фармакология)
Results of study of antiviral immunity indicators in patients with mucoviscidosis were presented. A significant antibody deficiency against a number of antigenically unrelated viruses — acute respiratory pathogens and Мycoplasma pneumonia, significantly lower levels of specific cellular antiviral immunity, massive prolonged viremia was identified. Viruses that cause exacerbation of bronchopulmonary process in patients with mucoviscidosis often continue to be detected in blood and in remission. In patients with mucoviscidosis a perverted immune response to viral infection has been revealed.Key words: mucoviscidosis, antiviral immunity, viremia.